Evaluasi Kapasitas Saluran Drainase Di Kecamatan Medan Kota Dan Medan Denai - Daulay, Ilmi Alfiah; Mahadewi, Catherine Honey; Simanjuntak, Rizky; Prayogo, Wisnu; Harahap, Rumilla (CV. SINAR HOWUHOWU, 2026)
Flooding occurs every rainy season on Air Bersih Street, which crosses Medan Kota and Medan Denai Districts. Rainwater tends to pond on the road surface rather than flow into drainage channels, indicating an imbalance between runoff discharge and channel capacity. This study aims to evaluate the capacity of existing drainage channels and identify the factors affecting their performance. Field surveys were conducted on 12 segments along ±3 km to measure channel width, depth, length, and sediment thickness. Maximum rainfall data for 2014–2023 from BMKG were analyzed using the Gumbel distribution and Mononobe method. Domestic wastewater discharge was calculated based on population data.The results show severe sedimentation with a total sediment volume of 780.3 m³. The planned runoff discharge reaches 2.51 m³/s, while domestic wastewater contributes only 0.086 m³/s (3.3% of total discharge). Comparison between total discharge and channel capacity indicates that only segment 10 has sufficient capacity (2.79 m³/s > 2.60 m³/s), while the other segments are inadequate. The main causes are lack of routine dredging, improper waste disposal, and insufficient channel dimensions. Therefore, immediate channel normalization, periodic sediment dredging, and public awareness on waste management are strongly recommended.